An Extended Technology Acceptance Model of QRIS Adoption: The Roles of Perceived Ease of Use and Financial Literacy - Syadin Alivia Yusuf; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2026)
This study examines the factors that drive consumers’ intention to use QRIS by focusing on the effects of perceived ease of use and financial literacy on perceived usefulness. A quantitative survey was conducted using primary data collected through an online questionnaire from 110 QRIS users in Indonesia, selected through purposive sampling. Data analysis was carried out using IBM SPSS Statistics, covering respondent profiling, instrument validity and reliability assessment, classical assumption diagnostics, regression analysis, mediation testing, and hypothesis evaluation. The empirical findings indicate that perceived ease of use and financial literacy significantly and positively influence perceived usefulness. Moreover, perceived usefulness is proven to be a significant predictor of intention to use QRIS. The mediation results further highlight perceived usefulness as a key mechanism through which perceived ease of use and financial literacy contribute to intention to use indirectly. Overall, the study suggests that increasing QRIS adoption should be supported not only by improving system usability and convenience, but also by strengthening consumers’ financial literacy to enhance their perceived value of using QR-based payments. These findings offer practical implications for payment service providers and policymakers in encouraging sustainable and inclusive digital payment usage.